Proteomic Analysis Of Prostate Carcinogenesis Induced By Heterocyclic Amine 2-Amino-1-Methyl- 6-Phenylimidazo[4,5-B]Pyridine (PhIP) Using In Vitro Model - Saifuddin, Siti Nazmin (2019)
2-amino-1-methyl-6-phenylimidazo[4,5-b]pyridine (PhIP) is the most abundant type of carcinogenic heterocyclic amine produced in cooked meat. This study aims to investigate the carcinogenic effect of human physiologically relevant concentration of PhIP on human prostate epithelial cell line, RWPE-1, at cellular and protein levels in prostate carcinogenesis. RWPE-1 cells were exposed to 10-7, 10-8, 10-9 or 10-10 M PhIP, diluted in 0.003%, 0.025% or 0.25% DMSO, with or without metabolic activation system. The methodologies used in this study were MTS assay for cytotoxicity and cell proliferation tests, Alamar Blue assay for cell proliferation test, cell transformation assay, invasion assay and shotgun proteomic.